DAMPAK PENERAPAN ATURAN KELAS TERHADAP KEAKTIFAN SISWA DALAM PROSES PEMBELAJARAN - Putriyani, Puput; Khairunnisa, Fildzah Nasywaa; Meida, Tasya; Halim, Kayla Agianisa; Permana, Hinggil (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Through in-depth interviews with principals and homeroom teachers, this research reveals a comprehensive discipline enforcement mechanism as well as a humanist approach in fostering student behavior. The results show that the implementation of school rules is built through systematic collaboration between principals, teachers, staff, and parents. Some of the main strategies implemented include: Formation of a collective agreement at the beginning of the semester, implementation of sustainable programs such as Teacher Working Group (KKG) and Study Group (KOMBEL), persuasive approach in sanctioning, and continuous communication with parents. The key findings of this study show that an effective discipline approach focuses not only on enforcing rules, but also on building student awareness. This is achieved through educational academic assignments, constructive discussions, and continuous monitoring. The sanctions applied are academic and psychological, rather than physical, with the aim of raising students' intelligence and awareness. The conclusion of this study states that success in implementing school rules is highly dependent on the active involvement of all stakeholders, flexibility in adjusting the rules, and commitment to the school